2000
DOI: 10.1034/j.1398-9995.2000.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of house‐dust‐mite allergen in homes of nonallergic people in Pavia, Italy

Abstract: In homes of nonallergic subjects in northern Italy, Der f 1 exceeded the threshold for sensitization in a high proportion of mattress samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…This has been demonstrated in various studies from different countries. 8,26,28,29 Therefore, although total mite allergen exposure will depend on other sources, we most likely provided valid allergen exposure estimates that are comparable across centers. Finally, we did not collect information on the sampled dust weight, and therefore could not express allergen levels per square meter of mattress surface.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This has been demonstrated in various studies from different countries. 8,26,28,29 Therefore, although total mite allergen exposure will depend on other sources, we most likely provided valid allergen exposure estimates that are comparable across centers. Finally, we did not collect information on the sampled dust weight, and therefore could not express allergen levels per square meter of mattress surface.…”
Section: Discussionmentioning
confidence: 96%
“…[2][3][4] D pteronyssinus has long been regarded the predominant house dust mite species in Europe, but during the last decade, it has become clear that in certain European areas, D farinae is common. [5][6][7][8][9] Identification of housing characteristics associated with dust mites is helpful to evaluate the effectiveness of allergen avoidance measures. Some studies have suggested that determinants for allergens of the 2 species are different.…”
mentioning
confidence: 99%
“…In the remaining samples, D. farinae and D. pteronyssinus were equally prevalent. Both D. farinae and D. pteronyssinus are present in homes in northern Italy, but D. farinae is the predominant species [47]. The predominant species reported in most studies in England and western Europe are D. farinae and D. pteronyssinus, but E. maynei and storage mites are also present [48][49][50].…”
Section: Mites and Allergen Found In Homesmentioning
confidence: 99%
“…However, mites are the most important source of allergens in settled house dust (5)(6)(7). The most prevalent mites found in the homes of Croatia (8,9) and worldwide (6,10) are Dermatophagoides pteronyssinus and Dermatophagoides farinae.…”
mentioning
confidence: 99%